Synthesis of Readily Available Fluorophenylalanine Derivatives and Investigation of Their Biological Activity - Kratky, Martin; Štěpánková, Šárka; Vorčáková, Katarína; Navratilova, Lucie; Trejtnar, Frantisek; Stolarikova, Jirina; Vinsova, Jarmila (My University, 2017)
A series of thirty novel N-acetylated fluorophenylalanine-based aromatic amides and esters was synthesized using N-(3-dimethylaminopropyl)-N0-ethylcarbodiimide or phosphorus trichloride in pyridine. They were characterized by spectral methods and screened against various microbes (Mycobacterium tuberculosis, non-tuberculous mycobacteria, other bacteria, fungi), for their inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) and cytotoxicity. All amino acids derivatives revealed a moderate inhibition of both cholinesterases with IC50 values for AChE and BChE of 57.88–130.75 mM and 8.25–289.0 mM, respectively. Some derivatives were comparable or superior to rivastigmine, an established drug. Phenyl 2-acetamido-3-(4-fluorophenyl)propanoate was identified as the selective and most potent inhibitor of BChE. The esterification and amidation of parent acids led to an improved BChE inhibition. The esters are better inhibitors of BChE than the amides. The introduction of NO2 and CH3 groups into aniline ring and CF3 moiety in phenol is translated into lower IC50 values. Seven compounds showed selectivity index higher than 10 for at least one cholinesterase. Especially the esters exhibited a mild activity against Gram-positive bacteria, mycobacteria and several fungal strains with minimum inhibitory concentrations starting from 125 mM. The highest susceptibility was recorded for Trichophyton mentagrophytes fungus.
Syntéza nově připravených derivátů fluorofenylalaninu a určení jejich biologické aktivity
Keywords: Fluorophenylalanine Derivatives; cholinesterases; Biological; Activity; fluorofenylalaninové deriváty; cholinesterázy; biologická aktivita